Energy States of Phosphorous Donor in Silicon in Fields up to 18 T - Bruno-Alfonso, A. [UNESP]; Lewis, R. A.; Hai, G. -Q.; Vickers, R. E. M. (Springer/plenum Publishers, 2010)
The evolution of the energy states of the phosphorous donor in silicon with magnetic field has been the subject of previous experimental and theoretical studies to fields of 10 T. We now present experimental optical absorption data to 18 T in combination with theoretical data to the same field. We observe features that are not revealed in the earlier work, including additional interactions and anti-crossings between the different final states. For example, according to the theory, for the "1s -> 2p (+)" transition, there are anti-crossings at about 5, 10, 14, 16, and 18 T. In the experiments, we resolve at least the 5, 10, and 14 T anti-crossings, and our data at 16 and 18 T are consistent with the calculations.
Keywords: Silicon; Phosphorous donor; Impurity levels; Zeeman splitting